A 'Common Food Policy' for Europe: How governance reforms can spark a shift to healthy diets and sustainable food systems. (October 2020) - De Schutter, Olivier; Jacobs, Nick; Clément, Chantal
Highlights: EU governance is ill-adapted to address the systemic nature of food system challenges. Unhealthy diets continue to generate significant social, economic, & environmental costs. An integrated food policy framework could help build healthy & sustainable food systems. Between 2016 and 2019, IPES-Food led a participatory process to develop an EU Common Food Policy blueprint. New governance approaches should build coherence across policy areas & governance levels, & ensure food democracy. Abstract: More than half of adults in the European Union (EU) are now either overweight or obese (53%). Non-communicable diseases (NCDs), many of which are diet-related, account for 70% of mortality in Europe and a growing share of healthcare costs. While eating habits have an important role to play in NCD prevention, consumption patterns across the EU are diverging significantly from recommended diets. There is growing consensus on the solution: a series of coordinated and wide-ranging policy interventions to build healthy 'food environments'. This article argues that EU governance structures remain ill-adapted to the systemic nature of this and other challenges in food systems (e.g. climate change, biodiversity loss, food poverty): conflicting objectives and missed synergies are identified between different policy areas (agriculture, trade, health, environment, etc.) and between different levels of governance (EU, national, local). An integrated food policy framework – a 'Common Food Policy' – is therefore required to meet the EU's public health and sustainability objectives. It identifies four distinct aspects of the governance shift required to promote healthy diets and build sustainable food systems in Europe: (i) coherence across policy areas; (ii) coherence across governance levels; (iii) governance for transition; and (iv) food democracy. Blueprints for a Common Food Policy are already emerging, and are ripe for consideration, development, and implementation by the European institutions.